2022
DOI: 10.14311/ap.2022.62.0352
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental study of water vapour condensation with high content of non-condensable gas in a vertical tube

Abstract: This article deals with the possibility of separating water vapour from flue gases after oxyfuel combustion using condensation processes. Those processes can generally be described as condensation of water vapour in the presence of non-condensable gases. Hence, the effect of noncondensable gas (NCG) on the condensation process has been theoretically and experimentally analysed in this study. The theoretical model was developed on the basis of the heat and mass transfer analogy with respect to the effect of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…The experimental results indicated that the condensation performance decreases significantly with the increasing volume fraction of air. Based on the theories of heat and mass transfer, Krempaský et al [18] proposed a condensation model of the water vapor with NCG. In their experimental verification, the mixture of water vapor and air flowed through a vertical tube, as the air proportion ranges from 0.230 to 0.620.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results indicated that the condensation performance decreases significantly with the increasing volume fraction of air. Based on the theories of heat and mass transfer, Krempaský et al [18] proposed a condensation model of the water vapor with NCG. In their experimental verification, the mixture of water vapor and air flowed through a vertical tube, as the air proportion ranges from 0.230 to 0.620.…”
Section: Introductionmentioning
confidence: 99%